EFFECTIVENESS OF BOARDS OF MANAGEMENT IN MANAGING PUBLIC PRIMARY SCHOOLS: A SURVEY OF KAHURO SUB COUNTY, MURANG’A COUNTY - Kariuki, Mburu Nicholas; Kathuri, Prof. Nephat J.; Mungai, Ms. Sarah (IJRDO - Journal of Applied Management Science, 2017)
A Board of management acts as a link between the school and the parents. It is supposed to give schools leverage with regard to having the parents given a stake in the leadership and governance of the schools. The study sought to find out the effectiveness of Boards of Management in Kahuro Sub-County, Murang’a County. The study observed that: all the head teachers considered the Boards of Management to have been involved in the administration and governance programmes within the schools. All of the head teachers were of the view that involvement of the schools management Boardmembers in financial management was enhanced. Furthermore they considered the BoM to have been involved in the supervision of teaching and learning activities in their respective schools